Performance Reporting: The Preferred "No Cost" Accountability Program - Joseph C. Burke; Henrik P. Minassians (Educational Considerations, 2003)
For the last six years, the Rockefeller Institute of Government at the State University of New York at Albany has been surveying the State Higher Education Finance Officers (hereafter referred to as budget officers) regarding state activities in higher education performance funding and budgeting.